Translation and validation of the high-school satisfaction scale (H-SatP Scale) in Peruvian students - Gonzales-Valdivia, Johana; Morales-García, Wilter C.; Saintila, Jacksaint; Huancahuire-Vega, Salomón; Morales-García, Mardel; RuizMamani, Percy G. (Frontiers in Education, 2022)
Risk behaviors in schoolchildren can negatively influence and affect their well-being. Therefore, it is necessary to have a validated tool to measure student satisfaction in specific areas of the school. The objective of this study was to adapt to Spanish and evaluate the psychometric properties of the H-Sat Scale in Peruvian students. The participants were 691 high school students between 11 and 18 years old (M= 13.96, SD 1.38) who were administered the H-Sat Scale. The scale was translated into Spanish (H-SatP Scale) using the forward and backward method. The scale presented adequate internal consistency for each of the 5 factors (ordinal α, CR, ω and H >70). Confirmatory analysis confirmed the five-dimensional structure (χ2 = 620.864, df=160; CFI = 0.982, TLI = 0.978, RMSEA = 0.065, SRMR = 0.032). this measurement tool could be used for the evaluation of interventions in school and health contexts to assess other aspects of well-being necessary for their development in school-age students.